Community-based participatory research in diabetes prevention programs - Khan, Raihan K; Misra, Ranjita (Social Determinants of Health, 2019)
Background: The purpose of this study was to determine how community-based diabetes prevention programs utilized the concept and contents of the Community Based Participatory Research approach. Methods: Keyword search in PubMed and Scopus electronic databases from January 1, 2000, to December 31, 2019, was conducted to search and extract peer-reviewed articles that included words “Community-Based Participatory Research (CBPR)” and “diabetes mellitus” in the title, abstract or in the main article. The initial search yielded 1122 articles. After the final screening, a total of 67 articles were extracted for review. Results: Findings suggested that an advisory board was used by most diabetes studies, especially for planning and reviewing the study protocol. However, they were not included in the data analysis and study result dissemination process. Furthermore, the majority of the studies that used CBPR were conducted in North America. Conclusion: Partnership approach to research on community-based diabetes programs that equitably involves community members and researchers can benefit communities. This approach should also be widely adopted globally.